Factors affecting the vaccination, public awareness and acceptance towards vaccine / Muhammad Akmal Suhaimi - Suhaimi, Muhammad Akmal (Faculty of Communication and Media Studies, 2018)
The purpose of this study was to examine the factors; awareness and acceptance associated with the intention to get vaccinated. A researcher used quantitative survey methods which involved 150 respodents. Purposive sampling has been used which those acknowledge on vaccines. The descriptive quantitative research study was conducted through a survey using questionnaire form. The questionnaire included socio-demographic characteristics, the independent variables which is factors that affecting vaccination (1) family characteristics-related, (2) health and health service utilisation, (3) communication, information, and knowledge, (4) political attitudes, and also the dependent variables (I) vaccines necessity and (2) awareness towards vaccines. A researcher use Reasoned Action Model Theory by Martin Fishbein and lcek Ajzen which is indicated to study towards perceptions, belief and behavior (action). The theory is practically implemented on the decision making process. The hypothesis testing gained by two different methods which indicated different result which is Pearson Correlation and Multiple Linear Regression. A cross-sectional survey and structured questionnaire were used for data collection. SPSSS ver. 23 software was used in the analysis. Based on the research by using Pearson Correlation method, the five listed null hypothesis is accepted based on Multiple Regression Method, there are two different reading which formed different results. The first result is based on the Beta value which shows the most significant relationship between independent towards dependent variables. Thus, the result indicated family characteristics-related (IV) (P=0.414) is the strongest relationship towards dependent variables vaccines acceptance (DV). However, based on the significant value in Coefficient Multiple Linear Regression analysis, the null hypothesis of vaccines acceptance (P=0.056), and awareness towards vaccines (P=0.365) is being accepted with the significant value below than p=0.05.